The Gulf States, China, and Central Asia's green energy sector: Interactions patterns, geopolitical dynamics, and implications for the EU and Germany - Dawud Ansari; Rosa Melissa Gehrung; Jacopo Maria Pepe (Stiftung Wissenschaft und Politik (SWP), 2025)
Central Asian economies, particularly Kazakhstan and Uzbekistan, are pursuing increasingly ambitious goals for renewable energy. Apart from China - an established player in the market - it has increasingly been Gulf countries that have been implementing respective projects, particularly Saudi Arabia and, to a lesser extent, the United Arab Emirates (UAE). Both China and Gulf countries seem to have found a cooperative approach that is based on sharing the Central Asian market along the value chain. This approach could be a blueprint for future Gulf-China relations, which have become relevant for global politics. Simultaneously, the dynamics also exemplify the growing number of energy and geopolitical dynamics over which Europe has little influence. For the European Union (EU) and Germany, the developments serve as a reminder: While intra-Asian dynamics are gaining importance, Germany and the EU risk being marginalised in matters concerning energy, climate, and geopolitics - and not just in Central Asia. In response, a more consistent Central Asia strategy is required, alongside a constructive and non-ideological approach towards relations with the Arab Gulf States.
Keywords: 320; Kazakhstan; Uzbekistan; China; Saudi Arabia; United Arab Emirates (UAE); EU; Germany; Central Asian market; Gulf-China relations; energy; geopolitical dynamics; ACWA Power Renewable Energy Holding; PowerChina; hydrogen; carbon capture and storage; climate technologies; fossil fuels; green energy